Squeezing, Bleaching, and the Victims' Fate: Wounds, Geography, Poetry, Micrology. Issue 1 (2nd January 2017) - Philo, Chris
Abstract : This article opens a dialogue between geohumanities and poetry—or, more broadly, creative writing—around the subject matters of violence and wounding. It considers what kinds of "poetry" might be usefully enrolled by the geoliterary critic, or even authored by the geographer-poet, in response to such subject matters. Difficult questions abound about what it means to author, hear, and read poetry that is engaged and enraged by instances of violence, trauma, and victimhood. One horizon for these questions is Adorno's ([1966] 1973) claim that "there can be no more poetry after Auschwitz, " and more particularly his elaboration and partial retreat from this claim in Negative Dialectics . Here, wary of attempts "at squeezing any kind of sense, however bleached, out of the victims' fate" (Adorno [1966] 1973, 361), he nonetheless concluded that "perennial suffering has as much right to expression as a tortured man to scream; hence it may be wrong to say that after Auschwitz you can no longer write poems" (363). This article explores Adorno's position, chiefly pursuing his arguments about the need for poetry—and indeed philosophy—that strives not for "purity" but precisely to be "soiled" and "spoiled, " never comforting, always disconcerting, never idealistically "transcendent, " always materialistically "micrological." Including reference to a short story by Borges and critique of poetry by the geographer Wreford Watson, the argument is further advanced by attending to Adorno's claims about another poet, Heine, sometimes regarded as a particularly "geographical" poet. The article concludes with final notes on possible implications for recasting work on wounded geographies as a species of applied micrology.